Patient and Public Engagement in Health Research: Learning from UK Ideas - Khatiwada, S.; Gautam, P.; Koju, A.; Niraula, B.; Khanal, G.; Sitaula, A.; Lamichhane, J.; Regmi, P.; van Teijlingen, E. (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
One of the new ideas in health and social care research in the UK is around involving patients and the general public in all aspects of research. This paper led by seven MSc students from Manmohan Memorial Institute of Health Sciences in Nepal. They attended Bournemouth University modules as part of the Erasmus+ exchange programme in 2022 and worked with two UK-based academics. The authors outline the thinking behind this process, and offer an example. They address its importance in improving the quality of the research as well as adding value to its societal relevance.